Phenyliodoso Acetate Oxidation of Cobalt(III) Bound and Unbound α-Amino Acids - Anbuselavan, C.; Sankaran, K.R. (Asian Journal of Chemistry, 2010)
The kinetics of phenyliodoso acetate (PIA) oxidation of cobalt(III) bound and unbound α-amino acids have been studied in aq. acetic acid in the presence of 1.00 M HClO4 at 50ºC. The reaction exhibits total second order kinetics, first order in each reactant. The rate of PIA oxidation is susceptible to polar influences. The introduction of substituents at the α-carbon atom in amino acids increase rate marginally while introduction of substituents at the amino nitrogen retard the rate considerably evidencing an initial attack by PIA at amino nitrogen. The formation of glyoxylatopentaamrninecobalt( III) complex during the PIA oxidation of glycinatopentaamrninecobalt( III) complex suggests cleavage of N—H and C—H bonds.